Clinical Management of Children and Adolescents with Neurofibromatosis Type 1 Like Phenotypes and Complex Behavioural Manifestations: A Multidisciplinary and Dimensional Approach. (31st December 2019) - Moscoso, Ana; Julien, Aurélie; Tanet, Antoine; Consoli, Angèle; Pagnard, Martine; Trevisan, France; Kemlin, Isabelle; Rodriguez, Diana; Cohen, David
Abstract : Introduction. Cognitive and behavioural problems associated with Neurofibromatosis type 1 (NF1) are common sources of distress and the reasons behind seeking help. Here we describe patients with NF1 or NF1-like phenotypes referred to a Tier 3 Child and Adolescent Psychiatry Department and highlight the benefits of a multidisciplinary assessment. Methods. Prospective data were gathered from NF1 patients aged 7–15 years, referred by the NF1 Referral Centre due to additional difficulties either in management or diagnosis. For the selected cases, we performed a psychiatric assessment, a tailored neuropsychological evaluation based on clinical demands and history, broad speech and motor skills evaluations if there were concerns regarding language, motor abilities and/or learning difficulties and autism specific evaluations, if clinically relevant. No exclusion criteria were applied. Results. Complex NF1 cases represented only 5% of the patients (11/224). Assessments revealed the complexity of NF1 phenotype and a variety of problems including learning difficulties, emotional problems and autism spectrum disorders. Specific evaluations of language, motor, attentional and neurovisual domains were essential to guide tailored intervention strategies. Conclusions. In terms of clinical implications, the heterogeneity of NF1 phenotypical manifestations needs to be considered when developing assessment and remediation approaches for children with complex NF1.